Long-term survival outcomes following resection of lung metastases (LM) from a colorectal primary. - Sangeetha Ramanujam; Catherine Dunn; Phillip Antippa; Suzanne Kosmider; Yat Hang To; Margaret Lee; Vanessa Wong; Susan Caird; Jeremy David Shapiro; Joseph James McKendrick; Hui-Li Wong; Brigette Ma; et al. (Journal of Clinical Oncology, 2022)
50 Background: Liver metastatectomy in oligometastatic colorectal cancer (CRC) can result in long-term disease control 1 . The benefit of resecting LM is unclear, with good survival outcomes from medical therapy (MT) alone and a recent randomised controlled trial failed to demonstrate an overall survival (OS) benefit 2 . Methods: We examined TRACC (Treatment of Recurrent and Advanced Colorectal Cancer), a multisite registry for metastatic colorectal cancer (mCRC) patients (pts) from September 2002 – July 2021, focusing on the longer-term outcomes for pts with lung only metastatic disease (LOM). Key clinicopathological, treatment and outcome variables were analysed. Survival outcomes were determined by Kaplan-Meier method. Results: Of 3928 pts, 341 (8.7%) had LOM. The median OS was significantly improved for LOM vs. all mCRC pts (44.5 months vs. 24.8 months, p =